Ensaios não destrutivos aplicados à madeira serrada e estruturas : técnicas potenciais para uso no Brasil - Cardin, Viviane de Salles (Universidade Federal de São Carlos, 2011)
The wood has many different characteristics, resulting, in part, of the conditions in which the tree grows. The physical conditions of the wood are also influenced by its complex internal structure, resulting in an anisotropic behavior. Within this variability, its best use and application can be reached through non-destructive methods. The non-destructive methodology is performed to verify the existence or inexistence of discontinuities or defects, without changing its later use. This work aims at presenting the non-destructive techniques in wood with potential use in Brazil. It also aims at applying the ultrasound technique in lumber pieces of Pinus sp of structural dimensions, with the purpose of verifying the accuracy of such technique, comparing it to the values obtained in destructive tests (static bending tests). The coefficient of determination (R2) obtained from the regression line between the static modulus of elasticity and dynamic modulus of elasticity with the use of ultrasound was 0.66, that allows affirming that this technique has accuracy in the assessment of mechanical pieces of wood.
Keywords: Construção civil; Madeira; Ensaios não destrutivos; Ultrassom; Wood; Non-destructive tests; Ultrasound; ENGENHARIAS::ENGENHARIA CIVIL::CONSTRUCAO CIVIL